New trends in assessing the prestress loss in post-tensioned concrete bridges - Zanini, Mariano Angelo; Faleschini, Flora; Pellegrino, Carlo (Frontiers in Built Environment, 2022)
The evaluation of the current prestress force represents often a challenging issue during the assessment of existing post-tensioned concrete (PTC) members. In this contribution, two case-studies are presented to show the efficiency of some experimental methods applied both to laboratory beams and to an in-service PTC bridge. First, the outcomes of an experimental campaign carried out on three PTC beams with a straight post-tensioned, non-grouted tendon are discussed. For each beam, three points bending tests (3PBT) were carried out applying increasing load steps until failure, and varying the prestress force; at each load step, non-destructive tests (NDTs) were performed, namely dynamic free vibration and ultrasonic tests. The variation of non-destructive parameters was evaluated as a function of the prestress force and of the structural damage. The second case study deals with a 50 years old PTC bridge, with grouted ducts. In this case, other than evaluating the existing geometry, structural details and material properties, the following NDTs were performed: endoscopies, tests based on stress release, i.e., both saw-cut and wire-cut tests, and lastly, X-Ray Diffractometries (XRD). Results indicate the high potential of this latter technique, which resulted more reliable and less invasive than the previous ones.